2023
DOI: 10.1101/gr.277947.123
|View full text |Cite
|
Sign up to set email alerts
|

An organism-wide ATAC-seq peak catalog for the bovine and its use to identify regulatory variants

Can Yuan,
Lijing Tang,
Thomas Lopdell
et al.

Abstract: We herein report the generation of an organism-wide catalogue of 976,813cis-acting regulatory elements for the bovine detected by the Assay for Transposase Accessible Chromatin using sequencing (ATAC-Seq). We regroup these regulatory elements in 16 components by nonnegative matrix factorization. Correlations between the genome-wide density of peaks and transcription start sites, between peak accessibility and expression of neighboring genes, and enrichment in transcription factor binding motifs supports their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 60 publications
(103 reference statements)
0
11
0
Order By: Relevance
“…Beside these candidate coding variants, we found evidence for regulatory variants in three QTLR on BTA5, 18 and 23. CS from these three QTLR did overlap with the catalogue of regulatory regions identified by ATAC-SEQ by Yuan et al [ 54 ]. For QTLR on BTA5 and 23, there was also association between the CS with cis-eQTL from a study conducted in blood and liver in Holstein [ 54 ] and evidence for regulatory effects in the cattle GTEx dataset [ 55 ].…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Beside these candidate coding variants, we found evidence for regulatory variants in three QTLR on BTA5, 18 and 23. CS from these three QTLR did overlap with the catalogue of regulatory regions identified by ATAC-SEQ by Yuan et al [ 54 ]. For QTLR on BTA5 and 23, there was also association between the CS with cis-eQTL from a study conducted in blood and liver in Holstein [ 54 ] and evidence for regulatory effects in the cattle GTEx dataset [ 55 ].…”
Section: Discussionmentioning
confidence: 71%
“…For the QTLR without obvious candidate coding variants, we also investigated whether SNPs in the CS overlapped with core and consensus segments from ATAC-seq peaks present in the catalogue from Yuan et al [ 54 ], with cis-eQTL reported in the same study or eQTL from the cattle GTEx study [ 55 ]. Contrary to the lead variant on BTA6, the CS variants on BTA5, consisting in six intronic variants from CCND2 (see Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations